A study of the knowledge and practice of lifestyle modification in patients with type 2 diabetes mellitus in Middelburg sub-district of Mpumalanga - Andrew Ekene Umeh; Lushiku Nkombua (South African Family Practice, 2018)
Introduction: Diabetes mellitus is one of the most common clinical conditions seen by family physicians in their daily practice. They are constantly confronted with the burden of caring for poorly controlled and poorly adherent patients presenting with preventable debilitating, disabling and mutilating complications. Lifestyle modifications in combination with medications have been proven to contribute to the prevention and delay of complications.